ANALYSIS OF PROFESSIONALLY IMPORTANT QUALITIES OF IT-SPECIALISTS - Гурська, О. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article analyzes the essence and theoretical basics of the concept of «professionally important qualities of the future IT-specialist» taking into account modern professional requirements to future professionals. It considers a number of domestic and foreign scientific, journalistic sources, where a special attention is paid to the concept of «professionally important qualities». As a result of study conducted on the basis of theoretical understanding scientific papers, the concept of «professionally important qualities of the future IT-specialist» is defined. We can state that professionally important qualities of these professionals are the complex of personal properties, individual psychophysiological and socially important qualities that contribute to the successful implementation of professional activity, the effective solution of professional problems, personal and professional growth and improvement